Upaya Meningkatkan Hasil Belajar IPA dengan menggunakan Model Example non Exmple dan Model Talking Stick pada Peserta Didik Kelas IV-A SDN 3 Langkai Palangka Raya 2016/2017: Efforts to Improve Learning Outcomes of Science by using Example Non Exmple Model and Talking Stick Model on IV-A Class Students in SDK 3 Langkai Palangka Raya 2016/2017 - Sakinatun Sakinatun; Muhammad Hamdani; Dedy Setyawan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
This study aims to: (1) Know how the activities of students during the learning process using the Example NonExample model and the Talking Stick Model. (2) Knowing whether there is an increase in student learning outcomes in science learning using the learning model Example NonExample and the Talking Stick Model. This research was conducted in the 1st week of April 2017 located at SDN-3 Langkai Palangka Raya, Jalan Temanggung Tandang Raya. This type of analysis is Classroom Action Research (CAR) with research subjects all IVA class students of Palangka Raya SDN-3 with 23 students, 13 men, ten women. Data collection techniques in this study used observations and tests. The data analysis techniques used qualitative and quantitative data analysis. The results of this study indicate that: (1) The activities of students both during science learning using the Example Non Example model and the Talking Stick model are shown by the acquisition of the results of observations, namely in the first cycle the total score is 91 with an average value of 3.64 and at cycle II the number of counts reached 95.5 with an average value of 3.82. (2) The use of Example Non Example learning models and Talking Stick models can improve student learning outcomes as indicated by the acquisition of an average value of 74.35 in the first cycle increased to 90.65 in the second cycle. Classical learning completeness also improved with an amount of 65.21% in the first cycle increased to 95.65% in the second cycle.